Investigation on Synergistic Bioactive Protection of LEA-motif and Trehalose on Insulin during Freeze-drying - Liu Li; Li Daixi; Guo Baisong; Pan Qi; Yu Huaxing; Chai Pei; Liu Baolin; Yang Chunsheng (Zhileng xuebao)
Due to the poor heat stability, insulin is easy to lose its bioactivity during storage. Bioactive protection of LEA-motif (LEAM) and trehalose towards insulin was investigated respectively and synergistically. High performance liquid chromatography method was used to study the proficiency of insulin and differential scanning calorimetry was used to study glass transition temperature. According to the results, both LEAM and trehalose can protect the bioactivity of insulin. The protective effect of LEAM is better than that of trehalose. That is to say that the bioactivity proficiency and heat stability of insulin within LEAM are better than those of insulin within trehalose. It is interesting that adding a bit trehalose can enhance the bioactive protection effect of LEAM towards insulin. During lyophilization, synergistic bioactive protection of LEAM and trehalose can not only enhance the stability of insulin, but also protect insulin from thermal degeneration. So such synergistic bioprotectants can be used to maintain the bioactivity of heat sensitive protein during lyophilization.